Impact of Extended Primary Surgery on Suboptimally Operable Patients With Advanced Ovarian Cancer. Issue 5 (June 2016) - Oseledchyk, Anton; Hunold, Lena Elisa; Mallmann, Michael R.; Domröse, Christian M.; Abramian, Alina; Debald, Manuel; Kaiser, Christina; Kiefer, Nicholas; Putensen, Christian; Pantelis, Dimitrios; Fimmers, Rolf; Kuhn, Walther; et al.
Abstract : Objectives: Extensive surgical efforts to achieve an optimal debulking (no residual tumor) in primary surgery of ovarian cancer are today's criterion standard in gyneco-oncologic surgery. However, it is controversial whether extensive surgery, including resections of metastases in the upper abdomen and bowel resections, is justifiable in patients with not completely operable lesions. Methods: All patients who had undergone surgery for ovarian cancer in the years 2002 to 2013 at our institution were viewed (n = 472). We retrospectively identified 278 operations for primary ovarian cancer. Ninety-six (35%) of the 278 patients showed postoperative tumor residuals and were included in this study. Results: Fifty-five (57%) of 96 patients underwent bowel resection, showing significantly higher complication rates (64% vs 39% minor complications, P = 0.017; 31% vs 9.8% severe complications, P = 0.013) compared with patients without bowel resections as well as no improvement in progression-free or overall survival (median overall survival, 19.5 vs 32.9; P = 0.382). Multiple anastomoses (≥2) were associated with higher rates for anastomotic leakage (16.7% vs 2.6%, P = 0.02) and a higher mortality (16.7% vs 0%, P = 0.04) compared with patients with only 1 anastomosis. Extensive surgery of the upper abdomen was not associated with a significant increase in complication rates. Conclusions: Because of the increased morbidity of bowel resections without any evidence for improvement of survival, we suggest to restrain from further resection of intestines if an optimal debulking seems not feasible after removal of the major tumor bulk.